Flow cytometric analysis of platelets mepacrine-labelled dense granules among individuals with mild bleeding symptoms - Muhsin, Azlina; Mohd Tohit, Eusni Rahayu; Md Noor, Sabariah; Abdul Karim, Faraizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Mild bleeding symptoms are commonly encountered in the general population & amongst individuals with platelet disorders. One of the possible causes is due to reduced number of dense granules synthesis in platelets and defective release of its contents. This study was aimed to evaluate platelets mepacrine-labelled dense granules storage and release using flow cytometry in healthy individuals and those presenting with mild bleeding symptoms. Methods: This study was conducted at the National Blood Centre (NBC) and Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM). Thirty- four individuals were recruited as controls (n=24) and patients (n=10). ADP-activated platelets and mepacrine-labelled dense granules was detected using flow cytometry. Results were expressed as mean fluorescent intensity (MFI) of mepacrine in resting and activated platelets; representing dense granules storage and release, respectively. Statistical analysis was considered significant if p ≤ 0.05. Results: There was a significant difference of mean MFI between resting (1284.3 ± 91.8) and activated platelets (1233.8 ± 107.8) of overall respondents with mean difference of 50.5 (p<0.01). However, there was no significant difference of mean MFI in resting and activated platelets between controls and patients was observed. Conclusion: Results indicated there is no secretion defects in platelet dense granules among patients in comparison with controls. Flow cytometry provides alternative way of dense granule assessment in patients presented with mild bleeding symptoms.